PRINSIP KESANTUNAN BERBAHASA DAL PRINSIP KESANTUNAN BERBAHASA DALAM INTERAKSI ANTARA SISWA DENGAN GURU DI SMP NEGERI 2 KRIAN: PRINSIP KESANTUNAN BERBAHASA DALAM INTERAKSI ANTARA SISWA DENGAN GURU DI SMP NEGERI 2 KRIAN - Erlin Istiyanti; Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2015)
Unity of language is a norm or ethics to communicate in society. Therefore, people will recognize it so that everyone who has social interactions will use language appropriately and politely. Unity of language alone is not enough, if it is considered to make people speak politely. The solution is to pay attention to the principles of language unity. Everyone must know and understand about this, including elementary, middle, and high school students. The researcher used a qualitative approach because this study wanted to explain and describe the use of language unity as seen from the interaction between students and teachers at SMP Negeri 2 Krian. The data of this research is conversation or student speaking between teachers and students in SMP 2 Krian. The data sources for this study were teachers and students at SMP Negeri 2 Krian. Based on data analysis, the researcher found several maxims in the interaction of students and teachers at SMP Negeri 2 Krian. The principle of unity is based on Lech which is explained as the unity of language maxims. The maxims include (1) Wisdom; (2) Generosity; (3) Approval; (4) Courtesy; (5) Agreement; and (6) Sympathy. Therefore, it can be concluded that the interaction between students and teachers at SMP Negeri 2 Krian is polite. If it occurs because the interaction between students and teachers has fulfilled the politeness principle as stated by the maxim translated by Leech.